Angiosarcoma in HIV-negative patients is not associated with HHV-8 - João Avancini; José Antonio Sanches; Andre Pires Zanata Cherubim; Renato Pazzini; Cristina Mendes de Oliveira; Laura Masami Sumita; Neusa Yuriko Sakai Valente; Claudio Sergio Pannuti; Cyro Festa Neto (Sociedade Brasileira de Dermatologia, 2016)
Abstract: BACKGROUND: Angiosarcoma is an aggressive, malignant neoplasm of vascular or lymphatic origin. Herpes virus 8 (HHV-8) is a member of the herpes family with a tropism for endothelial cells and it has been proven to induce vascular neoplasms, such as Kaposi's sarcoma. The role of HHV-8 in the pathogenesis of angiosarcoma has not been well defined. OBJECTIVE: To investigate the relationship between the presence of HHV-8 and angiosarcoma. METHODS: In this study, the team investigated the relationship between the presence of HHV-8, as determined by polymerase chain reaction, and angiosarcoma, using samples from patients with epidemic Kaposi's sarcoma as controls. RESULTS: While all control cases with epidemic Kaposi's sarcoma were positive for HHV-8, none of the angiosarcoma cases was. CONCLUSION: These findings support most previous studies that found no association between HHV-8 and angiosarcoma.